Fermentation Quality and in Vitro Nutrient Digestibility of Fresh Rice Straw-Based Silage Treated with Lactic Acid Bacteria - B Santoso; B Tj Hariadi; V Sabariah; T Sraun (Faculty of Animal Science, Bogor Agricultural University, 2014)
The aim of the experiment was to evaluate fermentation characteristics and in vitro nutrient digestibility of fresh rice straw-based silage ensiled with addition of epiphytic lactic acid bacteria (LAB) inoculant. The experiment was arranged in a completely randomized design, with 2 × 2 factorial arrangement of treatments. The first factor was the ratio of fresh rice straw (FRS), tofu waste (TW) and cassava waste (CW) consisted of two levels i.e., 40 : 20 : 40 and 40 : 25 : 35, on dry matter (DM) basis). The second factor was the level of LAB inoculant with two levels ie., 0 and 20 mL/kg FM. The treatments were (A) FRS + TW + CW with the ratio of 40 : 20 : 40, without LAB inoculant; (B) FRS + TW + CW with the ratio of 40 : 20 : 40 + LAB inoculant; (C) FRS + TW + CW with the ratio of 40 : 25 : 35, without LAB inoculant; (D) FRS + TW + CW with ratio of 40 : 25 : 35 + LAB inoculant. Results showed that addition of LAB inoculant in silage increased lactic acid concentration (P0.05) on chemical composition, fermentation quality of silage and in vitro digestibility. It was concluded that mixture silage with ratio of 40 : 20 : 40 with the addition of LAB inoculant had the best fermentation quality and nutrient digestibility than other silages.